Prevalence and risk factors for suicide attempts in prison - Favril, L; Shaw, J; Fazel, S (Elsevier, 2022)
Suicidal behaviour represents a substantial burden of morbidity and mortality in prisons worldwide. We aimed to synthesise the evidence on prevalence and risk factors for suicide attempts during incarceration. In this systematic review and meta-analysis, we searched four bibliographic databases for studies (published up to May 31, 2022) reporting on adults sampled from the general prison population who attempted suicide while incarcerated and an unselected comparison group. A total of 20 studies comprising 19,882 individuals (6.5% women) in 20 countries were eligible for inclusion. The pooled prevalence of suicide attempts during incarceration was 8.6% (95% CI 6.1–11.2) in men and 12.2% (95% CI 7.1–17.2) in women. Across all 36 risk factors studied, the strongest associations were found for suicidal ideation, previous self-harm, and markers of psychiatric morbidity. Prison-related risk factors included solitary confinement, victimisation, and poor social support while incarcerated. Sensitivity analyses indicate that risk factors for near-lethal suicide attempts are similar to those for suicide attempts more generally. In addition to providing a synthesis of previous work, our systematic review highlights several key limitations of the extant literature, which provide directions for future research.